An Investigation of Human Cortical Bone's Response to Mechanical Stimuli. (2015) - Wang, Yanan
Abstract: The response of human cortical bone to mechanical stimuli is investigated in this paper. Bone remodeling which is the underlying mechanism that underpins bone formation and absorption is mathematically modelled at cellular level, based on which the numerical analysis has been conducted. The control mechanism of mechanical bone remodeling at cellular level was investigated by means of an extensive parametric study on a theoretical model described in this paper. From a perspective of control mechanism, it was found that there are several control mechanisms working simultaneously in bone remodeling which is a complex process. Typically, an extensive parametric study was carried out for investigating model parameter space related to cell differentiation and apoptosis which can describe the fundamental cell lineage behaviors. After analyzing all the combinations of 728 permutations in six model parameters, we have identified a small number of parameter combinations that can lead to physiologically realistic responses which are similar to theoretically idealized physiological responses. The results presented in the work enhanced our understanding on mechanical bone remodeling and the identified control mechanisms can help researchers to develop combined pharmacological-mechanical therapies to treat bone loss diseases such as osteoporosis.